2020
DOI: 10.21203/rs.3.rs-83788/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity scores in COVID-19 pneumonia: a multicenter, retrospective, cohort study

Abstract: BackgroundIdentification of patients on admission to hospital with Coronavirus infectious disease 2019 (COVID-19) pneumonia who can develop poor outcomes have not yet ben comprehensively assessed.ObjectiveTo compare severity scores used for community acquired pneumonia to identify high-risk patients.DesignPSI, CURB-65, qSOFA and MuLBSTA, a new score for viral pneumonia, were calculated on admission to hospital to identify high-risk patients for in-hospital mortality. Area under receiver operating characteristi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Moreover, PSI and CURB-65 both performed well in the evaluation of patients' disease severity (Kappa = 0.69, P < 0.001). Our results are in consistency with those reported by Artero et al 9 and Satici et al 13 Thus our findings suggest that PSI and CURB-65 might be useful to predict the severity and mortality of COVID-19 pneumonia. A previous study showed that patients with COVID-19 pneumonia who had compromised respiratory status on admission were at a higher risk of developing severe disease and worse outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, PSI and CURB-65 both performed well in the evaluation of patients' disease severity (Kappa = 0.69, P < 0.001). Our results are in consistency with those reported by Artero et al 9 and Satici et al 13 Thus our findings suggest that PSI and CURB-65 might be useful to predict the severity and mortality of COVID-19 pneumonia. A previous study showed that patients with COVID-19 pneumonia who had compromised respiratory status on admission were at a higher risk of developing severe disease and worse outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…qSOFA score is simple, and qSOFA score ≥ 2 predicted the severity of COVID-19, with a sensitivity of 26.7%. 9 The study by Myrstad et al 10 showed that National Early Warning Score 2 (NEWS2) score was superior to qSOFA, Systemic Inflammatory Response Syndrome (SIRS) criteria and CRB-65 in predicting COVID-19 pneumonia severe and mortality. The finding from Ji et al 11 suggested that the CALL (comorbidity, age, lymphocyte, and Lactate Dehydrogenase; LDH) score could predict the progression risk in patients with COVID-19 pneumonia.…”
mentioning
confidence: 99%
“…Although 30-day mortality (3.8%) in our study was lower than recent reports ( Artero et al, 2021 ), Our findings have shown that 71% and 68.8% of our sample underwent CCI after admission to ICU with COVID-19 pneumonia had a CURB-65 and PSI scores of 1–2 and 1-3, respectively; with a relatively high need, for CCI (18.7%). Hence the need for clinical models for COVID-19 pneumonia based on other outcomes modified by in-patient care as compared to mortality.…”
Section: Discussioncontrasting
confidence: 71%
“…In some studies in the literature on COVID-19 pneumonia conducted to evaluate the need for ICU treatment, the mortality of patients with a CURB-65 score of 3 was found to increase and based on other studies in which the CUB-65 cut off value was found to be ≥2.5 in terms of mortality and invasive mechanical ventilation requirement, patients with a CURB65 score of 3 were evaluated as patients requiring ICU treatment [ [24] , [25] , [26] , [27] ]. Relying on these findings, patients in this study were divided into two groups as ICU need and non-ICU need.…”
Section: Methodsmentioning
confidence: 99%